Overview on child health, nutrition and food hazards during the first thousand days of life - Flavia Indrio; Julije Mestrovic; Angel Carrasco-Sanz; Mehmet Vural; Leyla Namazova-Baranova; Ida Giardino; Tudor Lucian Pop; Massimo Pettoello-Mantovani (Elsevier, 2022)
This article discusses the issue of food hazards and child health during the first thousand days of life. The aim is to raise the attention of decision makers, healthcare officers and professionals, including pediatricians, pediatric surgeons, obstetricians, nurses, midwives, dieticians and lactation consultants, on the importance of protecting infants and their families during a most critical period for the mother-child binomial. The conclusions emphasize the importance of encouraging the adoption of integrated strategies, useful at establishing adequate preventive efforts and a game-changing perspective shift in order to develop and adopt efficient monitoring strategies and procedures, able to minimize the risks due to hazards in food throughout the first thousand days of life, as a first line of prevention in children's health.